A STATISTICAL ANALYSIS OF TYPHOONS IN THE PERIOD 1951 - 2013 IN VIETNAM’S COASTAL ZONES - Toan, Du Van; Trinh, Nguyen Quoc; Tien, Pham Van; Toan, Luu Thi; Trung, Luu Thanh; Tien, Nguyen Ngoc (Vietnam Journal of Marine Science and Technology, 2014)
This article provided some evaluation methods of statistical analysis of typhoons in Vietnam. The results indicated that there were a total of 696 storms in Vietnamese sea for the period between 1951 - 2013, with the annual average more than 11 storms. Among them 327 storm approached coastline, bringing an average of 5.2 storms per year. Furthermore, hurricane season are likely to occur throught the month of July to September. The number of landing points were divided by 7 zones, taking account of decreasing gradient southward. The maximun, speed of storm was 58 metre per second and the maximum rainfall was over 400 mm. The variation mechanism of Vietnam typhoons in the future were withdrawn in order to support assurance of weather information and disaster prevention